Strategies for Strengthening Public Engagement in Monitoring Integrity Zone Development as an Effort to Achieve Good Local Governance - Sari, Lusi Puspika; Rusta, Andri; Reswita, Yefri; Syaiful, Syaiful; Khoiri, Muhammad Daffa; Alim , Husni (Pencerah, 2025)
This study aims to analyze strategies for strengthening public engagement in monitoring the development of integrity zones as an effort to improve local governance. A qualitative approach was employed through in-depth interviews and documentary analysis, with research conducted in Solok City and Padang Panjang City, West Sumatra Province. The findings indicate that public participation in monitoring integrity zones remains limited and largely relies on informal mechanisms. Traditional leaders play a crucial role in disseminating information and encouraging compliance with integrity policies, although their involvement is not yet fully supported by a strong legal framework. Strengthening their role through formal regulations could enhance the effectiveness of public participation. Moreover, broader community involvement has the potential to reduce corruption, promote transparency, and reinforce accountability in local governance. This study contributes by providing empirical insights into how local social structures can be leveraged to support public oversight and by offering practical recommendations for policymakers to enhance governance through the synergy between formal and informal actors.